Methods for determining the characterization of mashes with fiber for semi-finished products on the milk-protein base - Grek, Olena; Tymchuk, Alla; Tsygankov, Sergii; Onopriichuk, Olena; Savchenko, Alexander; Ochkolyas, Olena (My University, 2019)
The aim of the work is to develop effective methods that characterize the mixing of semi-finished products with potato fiber after heat treatment, to avoid excessive compaction of products and stabilization of qualimetric parameters. The article presents the main methods for determining the characteristics of mixtures with potato fiber for heat-treated semi-finished products.
Keywords: thermal processing; semi-finished products; potato fiber; кафедра технології молока і молочних продуктів